2012
DOI: 10.1038/pr.2012.118
|View full text |Cite
|
Sign up to set email alerts
|

High- and low-dose OPG–Fc cause osteopetrosis-like changes in infant mice

Abstract: Background Receptor Activator of Nuclear Factor-κB ligand (RANKL) inhibitors are being considered for use in children with osteogenesis imperfecta (OI). We sought to assess efficacy of two doses of a RANKL inhibitor, OPG-Fc, in a growing animal model of OI, the col1α2-deficient mouse (oim/oim) and its wildtype controls (+/+). Methods Treated mice showed runting and radiographic evidence of osteopetrosis with either high (20 mg/kg twice weekly) or low dose (1 mg/kg/week) OPG-Fc. Because of this adverse event,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Similar to most of the conditions mentioned in this review, these abnormalities result in altered bone quality and increased fracture risk. The condition may be caused by genetic abnormalities in regulators of osteoclast activity or by excessive suppression of bone turnover . Bone quality in osteopetrosis was characterized in the toothless rat and the osteopetrotic mouse by X‐ray diffraction and FTIRI; the latter showing microhardness was increased in osteopetrotic bone, the former demonstrated the persistence of small crystals.…”
Section: Bone Quality Changes In Diseasementioning
confidence: 99%
“…Similar to most of the conditions mentioned in this review, these abnormalities result in altered bone quality and increased fracture risk. The condition may be caused by genetic abnormalities in regulators of osteoclast activity or by excessive suppression of bone turnover . Bone quality in osteopetrosis was characterized in the toothless rat and the osteopetrotic mouse by X‐ray diffraction and FTIRI; the latter showing microhardness was increased in osteopetrotic bone, the former demonstrated the persistence of small crystals.…”
Section: Bone Quality Changes In Diseasementioning
confidence: 99%
“…Denosumab recognizes human and monkey, but not mouse or rat RANKL, so other recombinant RANKL inhibitors such as RANK‐Fc and OPG‐Fc have been used to inhibit RANKL in animal models . In this study, RANKL was inhibited by RANK‐Fc or OPG‐Fc, using dosing regimens intended to maximally inhibit osteoclasts throughout the 12‐week treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment ended 12 weeks after the transition time point. Doses of RANK-Fc and ALN were based on results of previous studies that showed increased bone mineral density without side effects using the same dose [1][2][3]. Weaning was carried out between 3 and 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The oim/oim mice, as a result of an inappropriate stop codon in the collagen I alpha 2 chain's gene, have a aI(I) 3 triple helix instead of the expected aI(1) 2 aI(2) helix [11] and provide a reproducible model with a moderate-to-severe (Type III) form of OI [34], including the presence of spontaneous fractures. Both alendronate (a bisphosphonate) and RANKFc, an inhibitory antibody to RANKL (receptor activator of nuclear factor-jB ligand), tested in short-term (8-week) studies showed a comparable reduction in the number of fractures relative to saline-treated oim/oim mice [2]. The bone composition assessed by Fourier transform infrared (FTIR) imaging after short-term alendronate treatment of the oim/oim mouse, however, was unchanged relative to saline-treated mice [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation